PERINGATAN DINI POTENSI HUJAN ES MENGGUNAKAN METODE SEVERE HAIL INDEX BERDASARKAN PENGAMATAN RADAR CUACA DOPPLER - Ali, Abdullah; Hidayati, Sabitul (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Hail is one of many extreme weather categories. The Indicator of hail occurrence is strong convective system of cloud. Meteorological instrument that has high temporal and spatial resolution to detect and predict hail occurrence is Doppler weather radar, and one of many methods that can be used is Severe Hail Index (SHI). SHI values is calculated based on flux values of hail kinetic energy, reflectivity, 0Â°C temperature profile height and -20Â°C temperature profile height. Hail occurrence at Jakarta 22nd of April 2014 gives SHI values 140,6 Jm-1s1, POSH (Probability of Severe Hail) 52,54%, and MEHS (Maximum Expected Hail Size) 32,9 mm, all values is calculated thirty minutes before hail occurred. Hail occurrence at Denpasar 16th of December 2010 gives SHI values 136,7 Jm-1s1, POSH (Probability of Severe Hail) 52,21%, and MEHS (Maximum Expected Hail Size) 56,6 mm, all values is calculated twenty minutes before hail occurred. Based on filed observation, POSH values is representative enough to predict hail occurrence. But there is an inappropriate between MEHS values and real condition. By using SHI method, early warning can be disseminated to reduce hail damage. Keywords : hail, Doppler weather radar, Severe Hail Index, early warning.